Aktivitas Antirayap Kulit Batang dan Akar Tumbuhan Kokosan (Lansium domesticum cv Kokossan) Terhadap Rayap Tanah (Coptotermes curvignathus Holmgren) - Fahma, Waninul; Alimuddin, Andi Hairil; Rudiyansyah, Rudiyansyah (Jurnal Riset Kimia, 2024)
Kokosan (Lansium domesticum cv Kokossan) is one of the Meliaceae family plants known to produce various compounds with various activities. The Meliaceae family is known to have fruit seeds with a bitter taste that can be utilized as an antifeedant in insects. However, research on the bioactivity and content of secondary metabolites in the roots and bark of kokosan as termiticides against subterranean termites has never been reported. This study aims to determine the content of secondary metabolite compounds and test the anti-termite activity of extracts and fractions of kokosan root and stem bark against Coptotermes curvignathus Holmgren termites. Root and stem bark powder were macerated separately using methanol solvent and then fractionated to obtain n-hexane, dichloromethane, ethyl acetate, and methanol fractions (residue). Each extract and fraction was fed to termites through cellulose paper at a concentration of 5% for 3 days. Based on the results of phytochemical tests on extracts and fractions from the roots and bark of kokosan, it is known to contain alkaloid, flavonoid, terpenoid, and phenolic compound groups. The results of the anti-termite activity test are based on the percentage mortality value obtained by the methanol extract of the most active root with a value of 97.2% and paper weight loss of only 6.92%. In the ethyl acetate fraction of the roots, mortality was 84.4% and paper weight loss was 2.38%, and the n-hexane fraction of the stem bark showed mortality of 87.6% and paper weight loss of 2.20%. The kokosan root obtained has the most active activity against Coptotermes curvignathus Holmgren.